(3GdJShjb ef NdGd YdGbJc HGdYedGA (B/s - (3SJhf, ejQdjfs; (3eGcJjfLQ, djR s; (3hhOchc, fjd s ((3GdbGgQI(B: s (3OGQGdaGQhb dfTQ hGdJhRjY(B, s, 2006)
(3GgejI JShjb GdefJLGJ GVGaI Gdi GdfeGPL GdNGUI HGOGQI GdYedGA(B, (3GdJYQa Ydi eWGdH GdYedGA(B, (3GdJYQa Ydi GdSjGSGJ GdJj SJfJgLgG GdTQcI(B, (3h cPG Jbjje fJGFL GdYed(B, (3GgejI HMK GhVGY GdShb(B, (3GdGMJaGX HGdYedGA h GcJSGH KbJge(B, (3GdYedjGJ h GdGLQGAGJ (B, (3OQGSI BOGA GdGaQGO(B, (3JcfhdhLjG GdJShb ef NdGd GdYdGbI HGdYedGA Hjf Gdjhe h GdZO(B, (3eSJbHd GdJShjb ef NdGd GdGJUGd HGYedGA GdcJQhfjG h aj GdGNjQ GdJNWjW dHQGeL GdJShjb ef NdGd GdYdGbI HGdYedGA(B.s
Keywords: (3GdJShjbs; (3GdYedGAs